IL-33 enhances the kinetics and quality of the antibody response to a DNA and protein-based HIV-1 Env vaccine - Sarkar, Sanghita (Vaccine, 2019)
Induction of a sustained and broad antibody (Ab) response is a major goal in developing a protective HIV-1 vaccine. DNA priming alone shows reduced levels of immunogenicity; however, when combined with protein boosting is an attractive vaccination strategy for induction of humoral responses. Using the VC10014 DNA and protein-based vaccine consisting of HIV-1 envelope (Env) gp160 plasmids and trimeric gp140 proteins derived from an HIV-1 clade B infected subject who developed broadly neutralizing serum Abs, and which has been previously demonstrated to induce Tier 2 heterologous neutralizing Abs in rhesus macaques, we evaluated whether MPLA and IL-33 when administered during the DNA priming phase enhances the humoral response in mice. The addition of IL-33 during the gp160 DNA priming phase resulted in high titer gp120-specific plasma IgG after the first immunization. The IL-33 treated mice had higher plasma IgG Ab avidity, breadth, and durability after DNA and protein co-immunization with alum adjuvant as compared to MPLA and alum only treated mice. IL-33 was also associated with a significant IgM Env-specific response and expansion of peritoneal and splenic B-1b B cells. These results indicate that DNA priming in the presence of exogenous IL-33 qualitatively alters the HIV-1 Env-specific humoral response, improving the kinetics and breadth of potentially protective Ab.